Analisis Sistem Pengukuran Getaran Mems Accelerometer ADXL345 - Indra Feriadi; Fajar Aswin; M Iqbal Nugraha (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
Vibration measurement technology using conventional sensors such as piezoelectric (PZT) Accelerometer is still expensive. Currently, many low-cost vibration measuring devices have been developed by using Micro Electro Mechanical System (MEMS) technology. This study aims to analyze the results of vibration measurement system MEMS Accelerometer ADXL345 with PZT Accelerometer. This research applies design and develop approach with comparative data analysis technique, that is comparing data of result of measurement of MEMS Accelerometer ADXL345 to PZT Accelerometer Vibroport80. The construction comprises the ADXL345 sensor connected to the Arduino Mega 2560 microcontroller operated by Widows operating system and programming language Arduino IDE 1.08. Testing of measurements at Bearing speeds of 500, 1000, and 1500 RPM with length of time measurements at 5, 10, and 20 seconds respectively. The analysis of the test results shows that the MEMS Accelerometer ADXL345 of vibration measurement system can measure, process and display vibration measurement data larger 3% than PZT Accelerometer and can provide the best measurement accuracy at 20 seconds measurement length of time.